(untitled) (Applied Biological Research, 2011)
The histological structure of ovary of the bat Taphozous kachhensis (Dobon) was studied during different phases of reproductive cycle. The female mature bats were collected; dissect-out and respective organ were fixed in bouins fixative for histological observation. During quiescence period no significant histological changes were observed in both ovaries, but during breeding period right ovary showed the development of Grafian follicle while in left ovary only some multilaminar follicles were seen. The study revealed that there was dominance of right ovary over left one; and right ovary seems functional during breeding cycle. The persistence of functional corpus luteum in the ovary of T. kachhensis throughout gestation indicated that the ovary may be the major source of progesterone, necessary for the maintenance of pregnancy in the species.